Blast Mitigation Strategies in Marine Composite and Sandwich Structures (Springer Transactions in Civil and Environmental Engineering,, 2018)
This book primarily focuses on methodologies to enable marine structures to resist high velocity impact loadings. It is based on invited talks presented at the recent India-USA workshop on "Recent Advances in Blast Mitigation Strategies in Civil and Marine Composite Structures" The book comprises content from top researchers from India and the USA and covers various aspects of the topic, including modeling and simulation, design aspects, experimentation and various challenges. These failure modes significantly reduce the structural integrity of the marine structures unless they are designed to resist such harsh loadings. Understanding the mechanics of these structures under harsh loadings is still an open area of research, and the behavior of these structures is not fully understood. The book highlights efforts to reduce the effects of blast loadings on marine composite structures. Intended for researchers/scientists and practicing engineers, the book focuses not only the design and analysis challenges of marine composite structures under such harsh loading conditions, but also provides new design guidelines.